A Comprehensive Review of Silicone Elastomers as an Extraoral Maxillofacial Material - Darshana Choubisa (Dental Journal of Advance Studies)
Among various extraoral maxillofacial materials, silicone is the most widely used extraoral maxillofacial material; however, research is currently being done to address its drawbacks and develop what may be called the “perfect maxillofacial prosthetic material.” This article has covered a variety of extraoral maxillofacial silicone materials, with an emphasis on how their characteristics change in response to diverse environmental factors. It also provides us with an opportunity to comprehend the main areas in which the materials are deficient and, thus, require modification in order to provide the greatest extraoral maxillofacial prosthesis to a person.